Enabling Systems Innovation in Climate Change Adaptation: Exploring th e Role for MEL - Gregorowski, Robbie; Bours, Dennis (Transformational Change for People and the Planet: Evaluating Environm ent and Development, 2022)
Traditional monitoring, evaluation, and learning (MEL) approaches, met hods, and tools no longer reflect the dynamic complexity of the severe (or “super-wicked”) problems that define the Anthropocene: climate ch ange, environmental degradation, and global pandemics. In late 2019, t he Adaptation Fund’s Technical Evaluation Reference Group (AF-TERG) co mmissioned a study to identify and assess innovative MEL approaches, m ethods, and technologies to better support and enable climate change a daptation (CCA) and to inform the Fund’s own approach to MEL. This cha pter presents key findings from the study, with seven recommendations to support a systems innovation approach to CCA:1.Promote and lead wit h a CCA systems innovation approach, engaging with key concepts of com plex systems, super-wicked problems, the Anthropocene, and socioecolog ical systems.2.Engage better with participation, inclusivity, and voic e in MEL.3.Overcome risk aversion in CCA and CCA MEL through field tes ting new, innovative, and often more risky MEL approaches.4.Demonstrat e and promote using MEL to support and integrate adaptive management.5 .Work across socioecological systems and scales.6.Advance MEL approach es to better support systematic evidence and learning for scaling and replicability.7.Adapt or develop MEL approaches, methods, and tools ta ilored to CCA systems innovation.